Pemberian Pijat Effluarage dalam Menurunkan Nyeri Spasme Otot pada Ibu Hamil Trimester III : Studi Kasus - Dalina Dalina; Riona Sanjaya; Helyani Helyani (Universitas Harapan Bangsa Purwokerto, 2023)
During pregnancy, pregnant women should maintain body balance from early to late pregnancy, so as not to occur unwanted disorders, one of which is muscle spasm. Labor pain can cause stress that causes excessive release of hormones such as catecholamines and steroids. Provide Continuous Midwifery Care with complementary interventions of effleurage massage. Method used in comprehensive care, type of descriptive research using the case study approach method. This comprehensive midwifery care is carried out in the Sumanda work area, Back District, Tanggamus Regency from March to April 2023.